ANALISIS POTENSI PENGEMBANGAN EKOWISATA PANTAI MANDEH KABUPATEN PESISIR SELATAN (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2015)
The tourism industry is the fault of the local revenue contributor, even foreign exchange earner of the country. Along with the tourist awareness of the environment and issues about sustainable development has contributed to the view of the importance of the principles of sustainable tourism. The principle of tourism is expected to maintain the quality of the environment, maintain the culture, empowering local communities and provide economic benefits to local communities, regions, and government. Mandeh beach is a tourist attraction that has a natural beauty, good food and friendly people. This study aimed to describe, analyze, and identify from ecotourism development based on internal factors and external factors. Internal factors include the development of ecotourism ecotourism development strengths and weaknesses. While external factors include the development of eco-tourism opportunities and threats. This study incorporates SWOT analysis method with AHP analysis. The analysis showed that the beach Mandeh have a positive potential for the development of ecotourism. Mandeh beach has a great opportunity and strength to be used as ecotourism.Key words: Potential, development of ecotourism